2011
DOI: 10.1177/0146167210392788
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analytic Investigation of the Relationship of State and Trait Anxiety to Performance on Figural and Verbal Creative Tasks

Abstract: Extensive research suggests when and how anxiety has debilitating or facilitating effects on routine cognitive tasks or motor tasks. However, research examining anxiety's relation to performance on creative tasks such as divergent thinking and artistic tasks is less conclusive despite a rather substantial literature. The authors' meta-analytic investigation of 59 independent samples finds that anxiety is significantly and negatively related to creative performance. In addition, the findings provide insights in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
84
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 93 publications
5
84
1
5
Order By: Relevance
“…In addition, the literature on anxiety suggests that procrastination may paradoxically impair creativity. Specifically, studies have documented that procrastination is positively correlated with anxiety (Haycock, McCarthy, & Skay, 1998;van Eerde, 2003), with anxious people tending to have low performance in divergent thinking (Byron & Khazanchi, 2011), an index that has been widely used in creativity research. Therefore, it seems sensible to assume that procrastination is indirectly harmful to creative performance due to anxiety.…”
Section: Literature Review Procrastination and Creativitymentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the literature on anxiety suggests that procrastination may paradoxically impair creativity. Specifically, studies have documented that procrastination is positively correlated with anxiety (Haycock, McCarthy, & Skay, 1998;van Eerde, 2003), with anxious people tending to have low performance in divergent thinking (Byron & Khazanchi, 2011), an index that has been widely used in creativity research. Therefore, it seems sensible to assume that procrastination is indirectly harmful to creative performance due to anxiety.…”
Section: Literature Review Procrastination and Creativitymentioning
confidence: 99%
“…Empirical studies have found that anxiety is negatively associated with creativity (Byron & Khazanchi, 2011;Friedman & Förster, 2008). Findings for emotion and creativity indeed indicate that negative emotion such as anxiety and fear are harmful to creativity (e.g., Baas, De Dreu, & Nijstad, 2008).…”
Section: Literature Review Procrastination and Creativitymentioning
confidence: 99%
See 2 more Smart Citations
“…High trait anxiety has been associated with poorer outcomes on a number of cognitive parameters, in both animals (Herrero, Sandi, & Venero, 2006) and humans (Byron & Khazanchi, 2011;Gawda & Szepietowska, 2016). Traditionally, anxiety has been associated with a hypersensitivity to threat (Spielberger, 1972).…”
mentioning
confidence: 99%